It is good to be average: Ecological correlates of breeding phenology in an Arctic seabird, Alle alle (Dovekie) ... - Ribeiro, Léa; Devogel, Marion; Grissot, Antoine; Kidawa, Dorota; Jakubas, Dariusz; Syposz, Martyna; Wojczulanis-Jakubas, Katarzyna (Zenodo, 2024)
Recognising importance of deviation from a population mean in an animal's behavior is not only necessary to understand the evolution and stability of the whole system but also to predict the future of a population in an altering environment. Arctic seabirds are expected to exhibit high synchronization in timing of breeding at the population level, due to highly seasonal and harsh environmental conditions. Nevertheless, even in such a highly synchronized system, there are always some earlier and later breeders, and what causes this inter-pair variation remains an intriguing question. Using a set of eight years of data on the dovekie (Alle alle), a small Arctic seabird, we examined potential drivers of the observed distribution of breeding phenology. We found that dovekie pairs were quite repeatable in their phenology, and preserved their phenological status, with their chicks hatching consistently before, during, or after the population median date for hatching, despite that calendar position of the median ... : Funding provided by: National Science CenterROR ID: https://ror.org/03ha2q922Award Number: 2017/25/B/NZ8/01417 Funding provided by: National Science CenterROR ID: https://ror.org/03ha2q922Award Number: 2017/26/D/NZ8/00005 Funding provided by: National Science CenterROR ID: https://ror.org/03ha2q922Award Number: 2021/40/C/NZ8/00043 ...